Chemical and structural evaluation of activated carbon prepared from jute sticks for Brilliant Green dye removal from aqueous solution - Asadullah, Mohammad; Asaduzzaman, M.; Kabir, M.; Mostofa, M.; Miyazawa, T. (Elsevier BV, 2010)
Activated carbons have been prepared from jute sticks by chemical activation using ZnCl2 and physical activation using steam for the removal of Brilliant Green dye from aqueous solution. The activated carbons and charcoal prepared from jute sticks were characterized by evaluating the surface chemistry, structural features and surface morphology. The maximum BET surface area was obtained to be 2304 m2/g for chemical activated carbon (ACC) while it is 730 and 80 m2/g for steam activated carbon (ACS) and charcoal, respectively. The FT-IR spectra exhibited that the pyrolysis and steam activation of jute sticks resulted in the release of aliphatic and O-containing functional groups by thermal effect. However, the release of functional groups is the effect of chemical reaction in the ZnCl2 activation process. A honeycomb-type carbon structure in ACC was formed as observed on SEM images. Although charcoal and ACC were prepared at 500 °C the ACC exhibited much lower Raman sensitivity due to the formation of condensed aromatic ring systems. Due to high surface area and high porous structure with abundance of functional groups, the ACC adsorbed dye molecules with much higher efficiency than those of ACS and charcoal.